The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1029/2022je007450
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance of Jezero Crater Floor: 2. Mineralogical Interpretation

Abstract: The Perseverance rover, Mars 2020 mission, landed on the surface of the Jezero Crater, on February, 18 th 2021. This Martian crater is suspected to have hosted a paleolake as evidenced by the numerous detections of aqueously-altered phases and thus is a promising candidate for the search for past Martian life. The SuperCam instrument, elaborated by a consortium of American and European laboratories, plays a leading role in this investigation thanks to its highly versatile payload providing rapid, synergistic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(98 citation statements)
references
References 127 publications
5
63
0
Order By: Relevance
“…The band at 1.9 μm (related to the presence of molecular water) is almost omnipresent in the targets of Séítah and Máaz with a very high BDNR, except in the holey rocks where it is practically absent probably because of photometric effects, see Mandon et al. (2022). On the other hand, the bands diagnostic of specific secondary phases between 2.1 and 2.5 μm are weaker: they are shallower than the 1.9 μm band, which explains the BDNR difference.…”
Section: Irs Spectral Performancementioning
confidence: 95%
See 3 more Smart Citations
“…The band at 1.9 μm (related to the presence of molecular water) is almost omnipresent in the targets of Séítah and Máaz with a very high BDNR, except in the holey rocks where it is practically absent probably because of photometric effects, see Mandon et al. (2022). On the other hand, the bands diagnostic of specific secondary phases between 2.1 and 2.5 μm are weaker: they are shallower than the 1.9 μm band, which explains the BDNR difference.…”
Section: Irs Spectral Performancementioning
confidence: 95%
“…Their detection corresponds to a signal drop on one or two spectral channels. However, most of the detections have a higher BDNR and are unambiguously identified (see Mandon et al., 2022).…”
Section: Irs Spectral Performancementioning
confidence: 98%
See 2 more Smart Citations
“…The diagnostic 2,000 nm pyroxene band is detected in Jezero by the CRISM imaging spectrometer from orbit, and Horgan et al (2020), using CRISM data to map both low and high Ca pyroxene, showed the region comprising the Máaz formation as being dominated by clinopyroxene. Mandon et al (2022aMandon et al ( , 2022b suggested that an intermediate Ca-pyroxene was a good candidate to explain some of the SuperCam infrared spectra of fine-grained regolith in the Máaz formation. Using both SuperCam LIBS and VISIR data, Cousin et al (2022) and Mandon et al (2022b) have shown that the fine-grained regolith at Jezero is a mixture of minerals containing pyroxene and plagioclase and has a more felsic composition than the coarse-grained regolith.…”
Section: Distinguishing Regolith Types By Chemistry and Mineralogymentioning
confidence: 99%